The teaching of Asian history as a section of the world history curriculum: the case of American high school teachers. Issue 1 (2nd January 2023) - Shin, Kyunghee
ABSTRACT: Many world history teachers in the US have tried to pluralize world history teaching from a more global perspective. This research focuses on how American teachers with an intention to change their current history teaching select Asian history topics and challenge traditional Western knowledge on Asia. I review world history scholarship to see how Asia is located within the curriculum, and literature to investigate the relations between knowledge and power dynamics. I individually interviewed eight teachers who teach a world history curriculum at public high schools in the Midwestern region of the US. Research findings showed that teachers felt comfortable in integrating ancient Asian history more into the history curriculum. For medieval history, teachers needed to obtain new knowledge for Asian history and they faced a dilemma in fundamentally challenging the Eurocentric framework. For recent history, teachers listed several pedagogical reasons for limited coverage of Asian history. These findings show that history teachers keep integrating Asian agency in their struggle towards globalizing history teaching.